Digitalisation in everyday urban planning activities: Consequences for embodied practices, spatial knowledge, planning processes, and workplaces - Gabriela Christmann; Martin Schinagl (Journal of Urban Management, 2023)
The article deals with the digitalisation of planning from a sociological perspective. The authors summarise results of their international empirical research in an analysis in which they place everyday digital planning practices at the centre of their considerations, where profound and intricate affects in planning occur at the level of embodied practices, spatial knowledge, planning processes, and workplaces. The authors examine the use of digital tools at different study sites and particularly discuss how the digitalisation of planners' actions through the use of Computer-Aided Design (CAD) programmes affects the way spaces are planned and how spatial knowledge is changing through the use of Geographic Information Systems (GIS). What is striking is that on the basis of digital practices, the relationships between planning actors are being refigured insofar as planning teams often work not only locally but at the same time globally networked and thus plan translocally. This refiguration through digitalisation (Knoblauch & Löw, 2020) in its social and spatial dimensions is also reflected in the design of workplaces (including the layouts of planning offices) as is shown in the article. Finally, it is outlined that risks and potentials for planning products are unfolding today through phenomena such as the digital datafication of spatial realities and translocal planning by the globally distributed members of planning teams.
Keywords: 320; Digitalisation; Planning practices; Planning processes; Spatial knowledge; Datafication